Pengaruh Literasi Keuangan, Financial Technology dan Green Accounting Terhadap Kinerja UMKM Di Kabupaten Ngawi - Fuguh Bagaskara Awalludin; Winarsih, Winarsih (Politeknik Raflesia Press, 2025)
This research investigates the influence of financial literacy, financial technology, and green accounting on the performance of Micro, Small, and Medium Enterprises (MSMEs) in Ngawi Regency, with a specific focus on the local tempeh chips industry. MSMEs are a critical component of the national economy, contributing significantly to employment and Gross Domestic Product (GDP). However, many MSMEs still struggle with sustainability and performance, especially post-COVID-19. This study adopts a quantitative approach, using a questionnaire distributed to 93 MSME owners. The analysis was conducted through multiple linear regression using SPSS version 29. The results indicate that financial literacy and financial technology have a positive and significant effect on MSME performance. This implies that business owners with higher financial knowledge and the ability to use digital financial services are better positioned to improve their business outcomes. On the other hand, the implementation of green accounting did not show a significant impact on performance. Many respondents lacked knowledge and awareness of environmental cost accounting, which is crucial for sustainable business development. The study recommends greater efforts in financial education and fintech adoption, along with raising awareness of environmental accountability, to enhance the performance and sustainability of MSMEs in regional economies.